Effect of Berberine Hydrochloride on Disposition Characteristics of Ciprofloxacin Hydrochloride and Its Mechanism in Yellow Catfish (Pelteobagrus fulvidraco) Following Combined Oral Administration - Tianfu Zhong; Xiangxuan Du; Yueyan Chen; Yongtao Liu (Fishes, 2025)
To investigate the effects and underlying mechanisms of the Chinese herbal medicine berberine hydrochloride (BBH) on the pharmacokinetics of the antibiotic ciprofloxacin hydrochloride (CIP) in yellow catfish (Pelteobagrus fulvidraco), this study established two experimental groups: CIP alone and CIP combined with BBH. After administering the two treatment groups, we analyzed the pharmacokinetic characteristics and tissue distribution of CIP in yellow catfish, as well as the differences in the expression levels of two key genes involved in drug disposition—ABCB4 (ATP-binding cassette subfamily B member 4, related to drug transport) and CYP3A40 (cytochrome P450 3A40, related to drug metabolism)—in the intestinal tract. The results demonstrated that co-administration of CIP and BBH increased the maximum concentration (Cmax) and area under the concentration–time curve (AUC) of CIP while reducing its total body clearance (CL/F). Regarding gene expression, the combined treatment significantly downregulated ABCB4 expression in the intestine at certain time points compared to CIP alone, whereas CYP3A40 expression showed a non-significant decreasing trend. These findings suggest that BBH may enhance the absorption of CIP in yellow catfish by suppressing ABCB4 expression, thereby improving therapeutic efficacy at the same dosage.